Caspase cleavage of Ets-1 p51 generates fragments with transcriptional dominant-negative function. - Choul-Li, S; Leroy, C; Leprivier, G; Laitem, C; Tulasne, D; Aumercier, M (2010)
Ets-1 is a transcription factor that plays an important role in various physiological and pathological processes, such as development, angiogenesis, apoptosis and tumour invasion. In the present study, we have demonstrated that Ets-1 p51, but not the spliced variant Ets-1 p42, is processed in a caspase-dependent manner in Jurkat T-leukaemia cells undergoing apoptosis, resulting in three C-terminal fragments Cp20, Cp17 and Cp14 and a N-terminal fragment, Np36. In vitro cleavage of Ets-1 p51 by caspase 3 produces fragments consistent with those observed in cells undergoing apoptosis. These fragments are generated by cleavage at three sites located in the exon VII-encoded region of Ets-1 p51. This region is absent from the Ets-1 p42 isoform, which therefore cannot be cleaved by caspases. In Ets-1 p51, cleavage generates C-terminal fragments containing the DNA-binding domain, but lacking the transactivation domain. The Cp17 fragment, the major cleavage product generated during apoptosis, is devoid of transcriptional activity and inhibits Ets-1 p51-mediated transactivation of target genes by competing with Ets-1 p51 for binding to Ets-binding sites present in the target promoters. In the present study, we have demonstrated that caspase cleavage of Ets-1 within the exon VII-encoded region leads to specific down-regulation of the Ets-1 p51 isoform during apoptosis. Furthermore, our results establish that caspase cleavage generates a stable C-terminal fragment that acts as a natural dominant-negative form of the full-length Ets-1 p51 protein.